2016
DOI: 10.1016/j.ijpharm.2016.02.027
|View full text |Cite
|
Sign up to set email alerts
|

In situ gelling systems based on Pluronic F127/Pluronic F68 formulations for ocular drug delivery

Abstract: This study evaluated the use of Pluronic F127 and Pluronic F68 as excipients for formulating in situ gelling systems for ocular drug delivery. Thermal transitions have been studied in aqueous solutions of Pluronic F127, Pluronic F68 as well as their binary mixtures using differential scanning calorimetry, rheological measurements, and dynamic light scattering. It was established that the formation of transparent gels at physiologically relevant temperatures is observed only in the case of 20 wt% of Pluronic F1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
128
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(148 citation statements)
references
References 37 publications
3
128
0
Order By: Relevance
“…By comparison between the results of in vitro and in vivo evaluations on GEL1 and GEL2, it could be rationally concluded that relative hydrophilic formulation led to faster hydrogel erosion, drug release and intravaginal elimination. Our finding is also consistent with a recently published study on ocular administration, which revealed that, under a fixed total polymer concentration, higher content of hydrophilic poloxamer 188 in the formulation resulted in faster removal from the corneal surface after application 28 . These phenomena could be explained by Marchetti group׳s work 29 , in which the authors found that the presence of hydrophilic additives like polyethylene glycol accelerated drug release from poloxamer-based hydrogel even at low concentration, and attributed the accelerated release to the higher osmotic pressure between the hydrogel and the dissolution medium created by the increased hydrogel hydrophilicity.…”
Section: Resultssupporting
confidence: 93%
“…By comparison between the results of in vitro and in vivo evaluations on GEL1 and GEL2, it could be rationally concluded that relative hydrophilic formulation led to faster hydrogel erosion, drug release and intravaginal elimination. Our finding is also consistent with a recently published study on ocular administration, which revealed that, under a fixed total polymer concentration, higher content of hydrophilic poloxamer 188 in the formulation resulted in faster removal from the corneal surface after application 28 . These phenomena could be explained by Marchetti group׳s work 29 , in which the authors found that the presence of hydrophilic additives like polyethylene glycol accelerated drug release from poloxamer-based hydrogel even at low concentration, and attributed the accelerated release to the higher osmotic pressure between the hydrogel and the dissolution medium created by the increased hydrogel hydrophilicity.…”
Section: Resultssupporting
confidence: 93%
“…[25][26][27] Our research group has previously synthesized a family of PBCs based on the amphiphilic Pluronic F127 triblock copolymer. [25][26][27] Our research group has previously synthesized a family of PBCs based on the amphiphilic Pluronic F127 triblock copolymer.…”
Section: Discussionmentioning
confidence: 99%
“…Also, KT has been used in form of hydrogel for nasal delivery using poloxamer 407 and carrageenan More recently, ofloxacin loaded Pluronic F127 and Pluronic F68 (20% w/v) in situ gelling formulation have been prepared and characterised. These deemed promising ocular formulation due to prolonged pre-corneal retention and good ocular tolerability using slug mucosal irritation assay and bovine corneal erosion study (Al Khateb et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%